Muhammad, profeternes segl og Daniels Bog - Sayyad Bach, Melissa; Høgenhaven, Jesper (Dansk Teologisk Tidsskrift, 2017)
In the Qur´an Muhammad calls himself “Seal of the Prophets”. The metaphor indicates that he sees himself as concluding and completing the line of prophets. This rare and unusual image seems to originate from Dan 9:24, which is strange, since the Book of Daniel or the prophet Daniel is never mentioned in the Qur´an. In this article, we attempt to trace the tradition behind the seal metaphor. This investigation brings us to Tertullian, who calls Christ the “Seal of all Prophets”, in a Christological interpretation of Dan 9:24. From here we survey the usage of seal metaphors in the Hebrew Bible, the Septuagint, the Vulgate, and the Book of Revelation. We briefly examine the occurrence of seal metaphors in Manichean tradition, and finally we analyze the reception of Daniel in the Syriac tradition.